2022
DOI: 10.3389/fonc.2022.1023110
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis based on multiple machine learning models to predict lymph node metastasis in early gastric cancer

Abstract: BackgroundEndoscopic submucosal dissection has become the primary option of treatment for early gastric cancer. However, lymph node metastasis may lead to poor prognosis. We analyzed factors related to lymph node metastasis in EGC patients, and we developed a construction prediction model with machine learning using data from a retrospective series.MethodsTwo independent cohorts’ series were evaluated including 305 patients with EGC from China as cohort I and 35 patients from Spain as cohort II. Five classifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 70 publications
0
1
0
Order By: Relevance
“…The importance of ML models are given in a few GC studies. These approaches were evaluated to predict the lymph node metastasis in GC patients [11][12][13][14][15][16][17] . Arai et al (2022) suggested ML method to predict the risk of GC in patients by information on gastric atrophy and intestinal metaplasia at the initial EGD 11 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of ML models are given in a few GC studies. These approaches were evaluated to predict the lymph node metastasis in GC patients [11][12][13][14][15][16][17] . Arai et al (2022) suggested ML method to predict the risk of GC in patients by information on gastric atrophy and intestinal metaplasia at the initial EGD 11 .…”
mentioning
confidence: 99%
“…Also, an advanced model was expanded to comprise radiomics clinical and features attributes to boost the performance of the model. Some studies also have advised ML methods to predict metastasis in GC patients [13][14][15][16][17] . Yang et al (2022) obtained some factors that depend on lymph node metastasis in GC patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers have developed ML models that predict the risk of LNM in patients with EGC [20][21][22][23][24]; however, these studies include many lesions satisfying the endoscopic curability criteria that have no risk of LNM. In contrast, we used only EGC data categorized as endoscopic curability C-2 (i.e., lesions at a high risk of LNM).…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning (ML), a fundamental branch of AI, excels in deciphering complex nonlinear associations among multidimensional features [ 14 ]. It has been extensively applied in the realm of healthcare, spanning areas such as medical diagnostics and the prediction of disease risks [ 15 , 16 ]. Numerous studies employ ML models to predict mortality risk in patients with conditions such as heart failure, surgical interventions, and sepsis [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%